ASEAN- Australia Trade Relations by Stages of Processing: Comparative Research - Phuong Ha Nguyen; Long Mong Hoang; Dung Duy Nguyen (Journal of Maritime Studies and National Integration, 2020)
ASEAN and Australia became the dialogue partner in 1974. Over 46 years of cooperation and development, ASEAN- Australia relations have achieved many good results, especially in recent years when two sides participate in several free trade agreements (FTAs) at bilateral levels and multilateral levels. In 2014, Australia and ASEAN formally became strategic partners, recognizing the importance of the relationship in building mutual benefits. Participation in FTAs and relationship upgrading has helped bilateral trade growth. In 2018-2019, Australia was the seventh-largest trading partner of ASEAN and ASEAN was one of Australia's top three trading partner, however, the two sides face many challenges such as the difficulties after the global crisis since 2009, the "spaghetti bowl" phenomenon of joining many agreements at the same time. Thus, to solve these problems, the production and exporting of comparative advantage goods by the stages of processing to participate in an ideal regional supply chain are very important. Based on the comparative theory and supply chain perspectives The paper compared revealed comparative advantage indexes of ASEAN countries and Australia from 2009 through 2018 to find which country in ASEAN is Australia's suitable partner from which provided the ideal effective supply chain distribution. After that, through trade value comparison, the paper examed if ASEAN countries and Australia specialized in production by stages of processing. From the results, appropriate recommendations were provided to enhance the trade relations between ASEAN and Australia.